Current Status of Contractual Conflict Resolution Mechanisms in the Colombian State - Reyes-Sarmiento, Lina Marcela; Guzmán-Suárez, Sara Patricia (DIXI, 2014)
The pretrial conciliation mechanism in Colombia arose as a speedier and more effctive alternative for conflct resolution compared to court proceedings. In the fild of administrative law, there are constant disputes between state agencies and private parties, particularly in signing and executing public contracts. Despite progress made through the creation of pretrial conciliation in state contracting (Law 640 of 2001), this legal form does not have the necessary cultural support, as there are few proceedings thatlead to a conciliatory settlement. This article presents the results of the current preliminary status of conflct resolution mechanisms in state contracting in Colombia, in which pretrial conciliation appearsto be the most frequently applied alternate resolution mechanism in Colombian law instead of resorting to the judicial system. The main discussions regarding alternative conflct resolution mechanisms are also presented, as well as in relation to the concept of pretrial reconciliation in administrative matters.
Keywords: Metropolitan Area of Bucaramanga; conciliation; public contracting; pretrial.